Factors Influencing Community Participation in Dam Failure Flood Risk Management: Challenges and Recommendations - Kaman, Zeittey Karmilla; Khanm, Tamanna; Mokhtar, Shaharina Bt.; Samsuddin, Siti Aqilah; Ali, Zuraidah (Amcolabora, 2024)
The risk of catastrophic floods resulting from dam failures, particularly when the dam is in proximity to densely populated areas, has sparked considerable concern among stakeholders, leading them to contemplate the potentially devastating consequences. Enhancing awareness and readiness among vulnerable communities in response to potential hazards stands as a widely acknowledged and pragmatic strategy to face the disaster with a minimum cost. The Sendai Framework advocates for the inclusive participation of community members in flood risk management (FRM) activities, aiming to enhance decision-making efficiency and improved mitigation efforts. The study has two main objectives: firstly, to identify key factors promoting active and successful community participation (CP) in FRM, and secondly, to explore potential challenges related to CP in dam failure FRM. Content analysis was used to review previous research and identify critical factors influencing effective CP in FRM. Building on the findings of content analysis and insights from prior studies on community-based dam failure FRM, the study addresses potential challenges and provides recommendations for adopting community- based interventions in dam failure FRM. This research contributes to the existing literature on FRM by offering strategic recommendations for managing dam failure floods and deepening our understanding of key factors in designing community-based interventions.